The state as a subject of regulatory impact on the development of the economy: opportunities and limitations (sociological analysis) - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2019)
On the basis of the institutional and historical-materialist approaches, a sociological perspective is proposed to explain the social mechanism of the regulatory influence of the state on the development of the economy. It is argued that the regulation of economic institutions and organizations is a complex, dialectical process of interaction between government bodies and social groups (classes) that realize their economic interests. In particular, an attempt is made to answer a number of topical questions about the sources and mechanisms for the development of economic institutions, those or other social groups interested in their appearance or disappearance, on the conformity or nonconformity of these interests with the economic needs of the country.
Keywords: regulating influence of the state; social groups; classes; institutional approach; economic and social institutions; organizations; social revolutions; social force; groups or classes; globalization